PEMBERIAN PUPUK ORGANIK DAN SUMBER NITROGEN HUMAT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN LIDAH BUAYA (Aloe vera L.) di LAHAN PASIR - Dedy Septiawan; Maria Theresia Darini; Darnawi Darnawi (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to determine the effect of rate of cow manure and the right source of humic nitrogen on the growth and yield of aloe vera plants in sand fields. The study was conducted in Cangkringan Hamlet, Poncosari, Srandakan, Bantul, D.I. Yogyakarta. The study was conducted from November 2017 - March 2018. The study was arranged in a Complete Randomized Block Design (RAKL), factorial 2 replications. The first factor is the dose of cow manure, consisting of two levels, namely 30 tons per ha and 45 tons per ha. The second factor, the type of nitrogen fertilizer supplemented with humic acid, consisted of urea + humic acid, ZA + humic acid, NPK + humic acid, KNO3 + humic acid. Analysis with variance at 5% real level, followed by Duncan Multiple Range Test (DMRT) and level of 5%. Observations were observed, namely leaf length, leaf width, leaf thickness, leaf fresh weight, leaf dry weight, and number of leaves. The results of this study show that there is no significant difference and the interaction between cow manure and humic nitrogen sources on all variables observed in the growth of aloe vera plants in sandy soil